«Хорезм балық өнимлери» акционерлик жәмийети 1-2-бөлим ҳәўизелери балықларының цестоза – Ботриоцефалёз кеселлиги - Якупова, П. (SCIENCE and SOCIETY, 2020)
The article presents data on the fish disease of the 1-2th department of the lake of the «Khorezm fish products» joint-stock company, with cestosis-Botriocephalosis.